Efficacy of a Plant-Microbe System: Pisum sativum (L.) Cadmium-Tolerant Mutant and Rhizobium leguminosarum Strains, Expressing Pea Metallothionein Genes PsMT1 and PsMT2, for Cadmium Phytoremediation - Tsyganov, Viktor E.; Tsyganova, Anna V.; Gorshkov, Artemii P.; Seliverstova, Elena V.; Kim, Viktoria E.; Chizhevskaya, Elena P.; Belimov, Andrey A.; Serova, Tatiana A.; Ivanova, Kira A.; Kulaeva, Olga A.; Kusakin, Pyotr G.; Kitaeva, Anna B.; et al. (Frontiers in Microbiology, 2020)
Two transgenic strains of Rhizobium leguminosarum bv. viciae, 3841-PsMT1 and 3841-PsMT2, were obtained. These strains contain the genetic constructions nifH-PsMT1 and nifH-PsMT2 coding for two pea (Pisum sativum L.) metallothionein genes, PsMT1 and PsMT2, fused with the promoter region of the nifH gene. The ability of both transgenic strains to form nodules on roots of the pea wild-type SGE and the mutant SGECdt, which is characterized by increased tolerance to and accumulation of Cd in plants, was analyzed. Without Cd treatment, the wild type and mutant SGECdt inoculated with R. leguminosarum strains 3841, 3841-PsMT1, or 3841-PsMT2 were similar histologically and in their ultrastructural organization of nodules. Nodules of wild-type SGE inoculated with strain 3841 and exposed to 0.5 µM CdCl2 were characterized by an enlarged senescence zone. It was in stark contrast to Cd-treated nodules of the mutant SGECdt that maintained their proper organization. Cadmium treatment of either wild-type SGE or mutant SGECdt did not cause significant alterations in histological organization of nodules formed by strains 3841-PsMT1 and 3841-PsMT2. Although some abnormalities were observed at the ultrastructural level, they were less pronounced in the nodules of strain 3841-PsMT1 than in those formed by 3841-PsMT2. Both transgenic strains also differed in their effects on pea plant growth and the Cd and nutrient contents in shoots. In our opinion, combination of Cd-tolerant mutant SGECdt and the strains 3841-PsMT1 or 3841-PsMT2 may be used as an original model for study of Cd tolerance mechanisms in legume-rhizobial symbiosis and possibilities for its application in phytoremediation or phytostabilization technologies.